2016
DOI: 10.17015/ejbe.2016.017.06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fiscal Decentralization on Non-Oil Economic Growth in a ResourceRich Economy

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…The question of whether this oil abundance is a “curse” or a “blessing” has been examined by Hasanov (2010) , who emphasizes that oil revenues mainly go to the nontradable sector. Further studies (e.g., Aliyev, 2019 , Aliyev and Mikayilov, 2016 , Aliyev and Nadirov, 2016 , Aliyev et al, 2016 , Dehning et al, 2016 , Gurbanov et al, 2017 , Hasanov, 2013b , Hasanov and Alirzayev., 2016 , Hasanov et al, 2016 , Hasanov et al, 2018 ) confirm that (oil revenue-financed) government expenditures have a positive impact on economic growth in the non-oil sector in Azerbaijan. Huseynov and Ahmadov (2013) provide a theoretical framework for this effect in an oil-exporting country and show that the procyclicality of fiscal policy is the major transmission channel of oil price shocks to the rest of the economy.…”
Section: Background On Azerbaijanmentioning
confidence: 86%
“…The question of whether this oil abundance is a “curse” or a “blessing” has been examined by Hasanov (2010) , who emphasizes that oil revenues mainly go to the nontradable sector. Further studies (e.g., Aliyev, 2019 , Aliyev and Mikayilov, 2016 , Aliyev and Nadirov, 2016 , Aliyev et al, 2016 , Dehning et al, 2016 , Gurbanov et al, 2017 , Hasanov, 2013b , Hasanov and Alirzayev., 2016 , Hasanov et al, 2016 , Hasanov et al, 2018 ) confirm that (oil revenue-financed) government expenditures have a positive impact on economic growth in the non-oil sector in Azerbaijan. Huseynov and Ahmadov (2013) provide a theoretical framework for this effect in an oil-exporting country and show that the procyclicality of fiscal policy is the major transmission channel of oil price shocks to the rest of the economy.…”
Section: Background On Azerbaijanmentioning
confidence: 86%
“…The technique is consisted of the following stages: (1) construction of an unrestricted ECM, (2) testing existence of cointegrating relationship or long-run association by using Wald-test (or the F-Test), (3) calculating the long-run coefficients by applying Bewley (1979) transformation if existence of cointegrating relationship among the variables is approved, (4) calculating long-run residuals and re-estimating the model by substituting long-run regressors by one lagged residuals. Detailed description of the estimation procedure is available in Pesaran et al (2001) as well as Hasanov et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the state budget expenditures for social-cultural activities and other expenses have positive-significant and negative-significant effect, respectively in their model. Hasanov et al (2016) also have studied the dependence of non-oil GDP on the non-oil employment, capital stock, total government revenues, total government expenditure, local government revenues and local government expenditure. They found that the effect of local government expenditures on non-oil GDP is negative and statistically significant at 10% significance level.…”
Section: Source: Own Compilationmentioning
confidence: 99%